Exploring Students’ Preferences Between Print and Digital English Learning Materials at MTsN Makassar - Dian Fera Pratiwi Sultan; Syarifuddin Dollah; La Sunra La Sunra (Hasanuddin University, 2025)
This study aims to investigates the preferences of junior high school students concerning printed versus digital English learning resources at MTsN Makassar. The research included 120 students from Grade IX who completed a structured questionnaire, along with 10 individuals in semi-structured interviews. In the process of data analysis, we employed descriptive and inferential statistical techniques for quantitative data, while qualitative responses underwent thematic evaluation. The research shows that scholars have a distinct liking for electronic learning content (M = 4.04, SD = 0.7) as opposed to their printed resources (M = 3.19, SD = 0.8). Students noted that characteristics like accessibility, interactivity, and engagement serve as important advantages of digital resources, while printed materials were credited with enhancing concentration and readability. Independent samples t-tests revealed no significant differences based on gender (p > .05); however, students with access to digital devices at home exhibited a significantly higher preference for digital formats (p = .040). The thematic analysis revealed three primary themes: (1) the engagement with digital media and the enjoyment it provides, (2) the motivation derived from easy access and constructive feedback, and (3) the essential task of aligning resource allocation with emerging challenges. Studies suggest that applying mixed learning techniques, combining internet-based and physical resources, can facilitate inclusiveness, amplify student interest, and improve the thoroughness of educational experiences in English Language Teaching (ELT).